Feasibility of applying the radio frequency identifier in the libraries of the National University of Asunción, 2021 (Journal on studies and research of academic knowledge, 2024)
The objective of the research is to analyze mechanisms implemented for the control of the bibliographic heritage of the libraries that make up the Network of University Libraries at National University of Asunción through the use of Radio Frequency Identification, and in this way verify its feasibility for control from the collection. It was based on a quantitative cross-sectional study and descriptive level. The population studied consisted of 12 libraries that make up the Network, a checklist was used as a data collection instrument, which was applied at the beginning of the 2021 period. The most outstanding results denote that 50% of the libraries have shelves closed, in addition, 83% use barcodes in bibliographic materials, considering that the range of book loss is between 3 to 5 materials per year, finally 8 libraries have an anti-theft electronic security system. In conclusion, the incorporation of systems that allow the automatic control of books to prevent theft and/or loss is still gradually being implemented in libraries.
Keywords: University Library; Automated library; Book collection; Anti-theft protection